Association between subjective cognitive complaints, balance impairment and disability among middle‐aged and older adults: Evidence from a population‐based cohort study. Issue 12 (3rd November 2022) - Tu, Raoping; Wang, Suhang; He, Huihui; Ding, Jiali; Zeng, Qingping; Guo, Lu; Li, Yueping; Xu, Tianwei; Lu, Guangyu
Abstract : Aim: To quantify the association between subjective cognitive complaints and balance impairment in relation to the occurrence of disability. Methods: In total, 6885 adults aged ≥45 who participated in the China Health and Retirement Longitudinal Study (CHARLS) were followed for 7 years. Subjective cognitive complaints were evaluated by self‐reported memory problems. Balance impairment was tested by side‐by‐side stand, semi‐tandem stand and full tandem stand. Disability was measured by activities of daily living (ADL) and instrumental activities of daily living (IADL). Multivariate logistic regression models were applied to test the joint effect between baseline subjective cognitive complaints and balance impairment on disability. The multiplicative interaction was examined. Results: A joint effect of experiencing both subjective cognitive complaints and balance impairment was identified, showing a 1.63‐fold higher risk of ADL and IADL disability than those experienced by neither of the two (odds ratio = 1.63, 95% confidence interval: 1.36–1.95). There was evidence of multiplicative interaction ( P = 0.004). Conclusions: Among middle‐aged and older people, the coexistence of subjective cognitive complaints and balance impairment may lead to a higher disability risk, which is much higher than the simple sum of the two individual effects. Future interventions are required to target these symptoms simultaneously to reduce the risks of disability. Geriatr Gerontol Int 2022; 22: 1025–1031 . Abstract : People with both subjective cognitive complaints and balance impairment had a higher risk of disability compared with those without either condition. In the future, interventions target on these symptoms to reduce the incidence of disability are required.